Comparative study in construction scheduling by using primavera P6 and microsoft project - Nor Farahin, Baharudin (2014)
Construction industry has played a very important role in contributing to the development of infrastructure and economic in Malaysia since the past. In 1998, Malaysia grew rapidly when the pride of Malaysia's landmark which is known as Petronas Twin Tower or Kuala Lumpur Convention Centre (KLCC) was built. The process to build KLCC took 7 years. In this context, it emphasized that the larger and complex of a project, the bigger the need to plan appropriate plan. Therefore, it is clear that construction is one of the challenging industries. Effective project plan need to be done before construction begin. Understanding, skills, experience and knowledge are the important elements to ensure a project will be done smoothly. Besides that, project manager need to ensure that the parties involved play their roles and responsibilities for the success of a project. Planning techniques and software selection should be well selected in order to achieve the optimum project planning. Several of techniques in planning are Critical Path Method (CPM), Bar Chart, Line of Balance (LOB) and so on. Meanwhile, the software used to develop a schedule would be Primavera, Microsoft Project, Asta Power Project, Deltek Power Plan and SureTrak. Obviously, project manager is one of the main elements in the smoothness of a project planning. The purpose of this study is to- compare the capability of two project management softwares namely Primavera P6 and Microsoft Project. Among the objectives to achieve this purpose are to identify feature and function of Primavera P6 and Microsoft Project and to develop scheduling by using both softwares. Besides that, interviews will be conducted with construction parties to identify their preference of scheduling software and the opinion to gain depth information related to Primavera P6 and Microsoft Project.